NILAI BUDAYA ON, GIMU, DAN GIRI DALAM NOVEL NIJUSHI NO HITOMI KARYA SAKAE TSUBOI - Ni Putu, Sri Radha Rani (Humanis, 2015)
This research entitled "An Cultural Values of The ‘On’, ‘Gimu’, and ‘Giri’ in The Novel Nijushi no Hitomi by Sakae Tsuboi". The purpose of this study was to know an culture value of ‘on’, ‘gimu’, and ‘giri’ in the novel Nijushi no Hitomi by Sakae Tsuboi. The study used descriptive analysis and informal method. The study used is the theory of anthropological literature by Suwardi Endraswara. In addition, this study also used the concept of ‘on’, ‘gimu’, and ‘giri’ by Ruth Benedict. The results of the analysis showed that the cultural values of ‘on’ are 1) the ‘on’ that is received from the parents; 2) the ‘on’ that is received from the emperor; 3) the ‘on’ that is received from the teacher; 4) the ‘on’ that is received from the state; and 5) the ‘on’ that is received from the ancestors. The cultural values of ‘gimu’ are 1) the obligation to parents; 2) the obligation to state; and 3) the obligation to job. The cultural values of giri are 1) the obligation to employer; 2) the obligation to people who are not family;3) the obligation to good name; and 4) the obligation to teacher
Keywords: anthropological literature, on, gimu, giri